Comparative chemoreactomic analysis of ornithine aspartate, S-ademethionine and ursodeoxycholic acid - I. Yu. Torshin; O. A. Gromova (Фармакокинетика и Фармакодинамика)
Purpose of the study. The pharmacological effects of ornithine are primarily due to its participation in the neutralization of ammonia and in the metabolism of amino acids. To clarify the mechanisms of action of ornithine, a chemoreactom analysis of ornithine aspartate was performed in comparison with S-ademetionine (S-AM) and ursodeoxycholic acid (UDCA). Methods. The effects of the investigated substances on the metabolism of urates (derivatives of uric acid), vasoactivity, vascular structure and cytoprotection were assessed by the method of chemoreactome analysis. Results. It was found that a decrease in blood urate levels is associated with inhibition by ornithine of the urate transporter URAT1 (ornithine – IC50 = 65 nM, S-AM – 1060 nM, UDCA – 94 nM) and xanthine oxidase (ornithine – IC50 = 910 nM, other molecules IC50 = 9655-11040 nM). Among the studied molecules, ornithine was distinguished by the most pronounced vasodilatory properties (probably associated with inhibition of adrenergic receptors: Kd = 35 nM, other molecules – 1108-1428 nM). The highest antidyslipidemic activity was also shown for ornithine (9.4 %) and S-AM (10.2 %), the lowest for UDCA (4.6 %). The antidyslipidemic effect of ornithine is associated with inhibition of endothelial lipase (IC50 = 258 nM for ornithine). The cytoprotective effects of ornithine are associated with an increase in glutathione synthesis, a decrease in the glutamatergic activity of neurons under conditions of glutamate stress, inhibition of prostaglandin D-synthase, and a decrease in the intensity of acute lymphocytic inflammation without immunosuppression. Conclusion. Thus, the results of the ornithine chemoreactom analysis indicate a significant expansion of the spectrum of the pharmacological effects of ornithine, including not only hepatoprotection, but also cardioprotection and nephroprotection.